Limited Knowledge of Chronic Kidney Disease and Its Main Risk Factors among Iranian Community: An Appeal for Promoting National Public Health Education Programs - Peyman Roomizadeh; Diana Taheri; Amin Abedini; Mojgan Mortazavi; Mehrdad Larry; Bahareh Mehdikhani; Seyed-Mojtaba Mousavi; Farid-Aldin Hosseini; Aidin Parnia; Manouchehr Nakhjavani (Kerman University of Medical Sciences, 2014)
Background The aim of this survey was to explore the baseline knowledge of the Iranian community about Chronic Kidney Disease (CKD) definition and its two main risk factors, i.e. diabetes and hypertension. This study also introduced a model of public education program with the purpose of reducing the incidence of CKD in high-risk groups and thereby decreasing the economic burden of CKD in Iran. Methods This cross-sectional study was conducted on world kidney day 2013 in Isfahan, Iran. Self-administered anonymous questionnaires evaluating the knowledge of CKD and its risk factors were distributed among subjects who participated in a kidney disease awareness campaign. Chi-square test and logistic regression analysis were used to examine the differences in the level of knowledge across different socio-demographic groups. Results The questionnaires were completed by 748 respondents. The majority of these respondents believed that "pain in the flanks" and "difficulty in urination" was the early symptoms of CKD. Roughly, 10.4% knew that CKD could be asymptomatic in the initial stages. Only 12.7% knew diabetes and 14.4% knew hypertension was a CKD risk factor. The respondents who had a CKD risk factor (i.e. diabetes and/or hypertension) were significantly more likely than respondents without CKD risk factor to select "unmanaged diabetes" [Odds Ratio (OR)= 2.2, Confidence Interval (CI) (95%): 1.4-3.6] and "unmanaged hypertension" [OR= 1.9, CI(95%): 1.2-3.0] as "very likely to result in CKD". No more than 34.6% of all respondents with diabetes and/or hypertension reported that their physician has ever spoken with them about their increased risk for developing CKD. Conclusion The knowledge of Iranian population about CKD and its risk factors is low. Future public health education programs should put efforts in educating Iranian community about the asymptomatic nature of CKD in its initial stages and highlighting the importance of regular renal care counseling. The high-risk individuals should receive tailored education and be encouraged to adopt lifestyle modifications to prevent or slow the progression of CKD.